2016
DOI: 10.1161/circresaha.116.309799
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Proliferation of a Subset of Differentiated, yet Plastic, Medial Vascular Smooth Muscle Cells Contributes to Neointimal Formation in Mouse Injury and Atherosclerosis Models

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
454
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(481 citation statements)
references
References 33 publications
26
454
1
Order By: Relevance
“…While we were finalizing our analysis, Chappell et al reached a similar conclusion based on a comprehensive analysis of the clonal structure of SMCs in Myh11-CreER T2 Confetti Apoe -/-mice after 16-19 weeks of high-fat diet (22). The reported clonal structure in that experiment were, however, simpler than the one we found, with the far majority of plaques only containing SMCs of 1 or 2 Confetti colors in the setting of a higher medial SMC recombination efficiency (70%-95% medial SMCs) (for similar analysis of our data see Supplemental Figure 4).…”
Section: Clonality and Phenotype Of Non-cap Smcssupporting
confidence: 56%
See 1 more Smart Citation
“…While we were finalizing our analysis, Chappell et al reached a similar conclusion based on a comprehensive analysis of the clonal structure of SMCs in Myh11-CreER T2 Confetti Apoe -/-mice after 16-19 weeks of high-fat diet (22). The reported clonal structure in that experiment were, however, simpler than the one we found, with the far majority of plaques only containing SMCs of 1 or 2 Confetti colors in the setting of a higher medial SMC recombination efficiency (70%-95% medial SMCs) (for similar analysis of our data see Supplemental Figure 4).…”
Section: Clonality and Phenotype Of Non-cap Smcssupporting
confidence: 56%
“…It may also be explained by other differences between models, time points, and arterial locations. The effect of the Confetti transgene on the atherosclerotic process or the particular architecture of the fibrous cap was not analyzed directly in the paper by Chappell et al (22). More precise estimates of the number of medial SMCs that goes into forming the plaque SMC population in different atherosclerosis models and at different time points could be obtained using mosaic mice with more recombination outcomes than the hemizygous Confetti mice used by Chappell et al and us.…”
Section: Clonality and Phenotype Of Non-cap Smcsmentioning
confidence: 97%
“…4 Furthermore, limited labeling of SMCs has shown the existence of intralesional clonal patches that arise from SMCs. 3 This study was recently extended by Chappell et al 9 who used an elegant multicolor lineage tracing reporter to conclusively demonstrate the clonal expansion of SMC-derived cells. Although mechanistic studies remain to be completed, it is plausible that these monoclonal foci of dedifferentiated SMCs arise from either (1) overgrowth of a hyperproliferative cell that simply outcompetes other cellular populations, (2) expansion of a clone, which is able to tolerate a lesional environment that is toxic to other cell types, or (3) active suppression of neighboring cells (eg, via juxtacrine factors) by the dominant/selected clone (Figure 1).…”
Section: Clonal Origins For Plaque-resident Cells?mentioning
confidence: 92%
“…Recent studies using SMC-specific promoters such as Myh11 and SM22 to mark and lineage trace SMCs within atherosclerotic lesions found that SMCs lose their characteristics and give rise to cells that exhibit phenotypes of other cell lineages, including macrophages and mesenchymal stem cells (MSCs) [90, 91•, 92]. Interestingly, using Confetti mice, it was shown that SMCs that lose SMC characteristics and undergo transition to macrophage phenotypes also begin to proliferate and clonally expand within atherosclerotic plaques, thus exacerbating plaque growth [93].…”
Section: Media and Adventitia-smooth Muscle And Perivascular Cellsmentioning
confidence: 99%